Measuring and analysing standardisation in the Hungarian hotel sector - Gyurácz-Németh,Petra (2018)
In tourism and the hotel sector standardisation is sometimes an advantage and other times a disadvantage, though it has been mentioned several times. This research explores the topic of standardisation in the Hungarian hotels. The paper determines the level of standardisation in hotels and the extant of the relationship between the level of standardisation and the hotel affiliation, the Hotelstars Union membership, the number of rooms and the star rating. There are 81 questionnaires filled out by hotel general managers of those hotels which belong to the Hungarian Hotel and Restaurant Association. Only the three-, four- and five-star hotels were questioned by this survey. The results show that the level of hotel standardisation depends on the hotel chain membership but only weakly by 5%. There are also proven significant relationships with the Hotelstars Union membership, the number of rooms and the star rating of the hotels.